3E 1D Architecture Maps Teacher Policy Coherence Toward 2045: Arsitektur 3E 1D Memetakan Koherensi Kebijakan Guru Menuju 2045 - Muryadi Muryadi; Fathur Rokhman; Eko Handoyo (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Teacher professionalism is central to national educational quality because policy aspirations are tested through classroom learning and long-term citizen development. Specific Background Indonesia has invested in certification, professional education, competency standards, professional organizations, digital platforms, and development programs, yet these instruments remain unevenly connected across recruitment, induction, appraisal, welfare, career pathways, leadership, and local governance. Knowledge Gap Existing teacher-quality initiatives are often treated as isolated programs rather than an integrated policy architecture that links equity, expertise, ecosystem support, and digital governance. Aims This article formulates the 3E 1D architecture as a coherent conceptual-operational framework for developing teacher quality and competence toward Golden Indonesia 2045. Results The integrative policy review of 60 international, Indonesian, regulatory, and theoretical sources produced four findings: teacher reforms are present but weakly integrated; compliance-oriented policy logic needs repositioning toward professional-capital development; each pillar requires concrete instruments, including a teacher-equity index, practice-based micro-credentials, professional learning communities, district coaching systems, strengthened professional organizations, and interoperable teacher portfolios; and implementation depends on data readiness, regional capacity, workload reduction, sustainable financing, and ethical digital governance. Novelty The article reframes teacher policy as a multi-level architecture that connects national standards, local support, school leadership, teacher wellbeing, professional organizations, and evidence-based professional learning. Implications Policymakers can use the 3E 1D model as a policy-design checklist, while future studies should validate it through Delphi inquiry, policy simulation, and pilot implementation across diverse contexts. Highlights • Reform instruments exist, but integration across governance levels remains weak.• Professional capital requires equity indexes, micro-credentials, learning communities, coaching, organizational support, and interoperable portfolios.• National scaling requires empirical validation, regional readiness, workload reduction, sustainable financing, and ethical data governance. Keywords Teacher Professionalism; Policy Architecture; Professional Capital; Digital Governance; Professional Learning